The Mediterranean diet could be an exceptional support for patients with chronic renal disease - Cacciabaudo, Francesco; Altomare, Roberta; Palumbo, Vincenzo Davide; Damiano, Giuseppe; Fazzotta, Salvatore; Gulotta, Leonardo; Lo Monte, Giulia; Maltese, Francesco; Lo Monte, Attilio Ignazio (Progress in Nutrition, 2020)
Chronic renal disease (CKD) is a social problem affecting millions of patients characterized byloss of renal function and related to metabolic diseases. The approach from the dietary point of view to thisproblem could be a perfect strategy to slow down the progression of the disease and at the same time theproblems of malnutrition typical of CKD. Several studies show that the Mediterranean diet (MD) may playa key role in the control of the early stages of the disease. Even if the MD showed to be the best diet for thecontrol of metabolic diseases and for the general well-being, in the case of the patient with CKD, should beadapted in what is called the DASH diet, characterized by the typical roles of the MD but with a controlledintake of minerals and proteins.